2008
DOI: 10.1177/147323000803600602
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine and Chondroitin for Osteoarthritis

Abstract: Osteoarthritis (OA) is a common, chronic disease that most frequently affects the knees and is a major cause of disability in the elderly. It is characterized by progressive cartilage loss, accompanied by secondary changes such as osteophyte formation and calcium deposition. Inflammatory processes are also involved, leading to stiffness and pain, for which patients seek treatment. Conventional treatment includes analgesics or non-steroidal anti-inflammatory drugs, however life-style changes should also be reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 45 publications
(58 reference statements)
1
61
0
2
Order By: Relevance
“…10 Glucosamine and chondroitin work slowly, taking a few weeks to become effective and should be given for at least 4 weeks before an assessment is made. 18 The evidence for glucosamine, chondroitin and their combination is reviewed below and confirms their efficacy and safety in the treatment of OA.…”
Section: Ec Huskisson a Holistic Approach To Pain Management In Osteomentioning
confidence: 99%
See 2 more Smart Citations
“…10 Glucosamine and chondroitin work slowly, taking a few weeks to become effective and should be given for at least 4 weeks before an assessment is made. 18 The evidence for glucosamine, chondroitin and their combination is reviewed below and confirms their efficacy and safety in the treatment of OA.…”
Section: Ec Huskisson a Holistic Approach To Pain Management In Osteomentioning
confidence: 99%
“…54 Because many of the glucosamine studies have been large scale and for long periods of time, it is not surprising that a meta-analysis provided little additional information. 18 Poolsup et al 55 showed symptomatic relief and delayed progression of knee OA. The risk of disease progression was reduced by 54%, while glucosamine sulphate caused no more sideeffects than placebo.…”
Section: Ec Huskisson a Holistic Approach To Pain Management In Osteomentioning
confidence: 99%
See 1 more Smart Citation
“…It also increases the synthesis of collagen. 88 Boron appears to participate in hydroxylation reactions, which play a role in the synthesis of steroid hormones and vitamin D. 59 Low boron intake results in impaired bone health and immune response.…”
Section: Silicon and Boronmentioning
confidence: 99%
“…It also possesses anti-tumor properties and has also been proposed for the treatment of autoimmune diseases. Glucosamine which is a derivative of NAG, has been shown to regenerate joint cartilage and is been used extensively in the treatment of osteoarthritis [7]. Presently, NAG is being derived using chemical processes by heating chitin in concentrated hydrochloric acid, which poses great technical and environmental concerns [8].…”
Section: Introductionmentioning
confidence: 99%